Current Researches on Nanodrug Delivery Systems in Bladder Cancer Intravesical Chemotherapy - Lu, Yilei; Wang, Siqi; Wang, Yuhang; Li, Mingshan; Liu, Yili; Xue, Dongwei (Frontiers in Oncology, 2022)
Bladder cancer is one of the most common malignant tumors in urinary system. Intravesical chemotherapy is a common adjuvant therapy after transurethral resection of bladder tumors. However, it has several disadvantages such as low drug penetration rate, short residence time, unsustainable action and inability to release slowly, thus new drug delivery and new modalities in delivery carriers need to be continuously explored. Nano-drug delivery system is a novel way in treatment for bladder cancer that can increase the absorption rate and prolong the duration of drug, as well as sustain the action by controlling drug release. Currently, nano-drug delivery carriers mainly included liposomes, polymers, and inorganic materials. In this paper, we reveal current researches in nano-drug delivery system in bladder cancer intravesical chemotherapy by describing the applications and defects of liposomes, polymers and inorganic material nanocarriers, and provide a basis for the improvement of intravesical chemotherapy drugs in bladder cancer.